Electrospun Polyurethane/Loess Powder Hybrids and Their Absorption of Volatile Organic Compounds - Jun Cong Ge; Jeong Hyeon Kim; Nag Jung Choi (Advances in Materials Science and Engineering)
We investigated the effects of composite electrospun polyurethane (PU)/loess powder (LP) fibers for absorption of volatile organic compounds (VOCs) from air. PU films containing different amounts of LP (0, 10, 30, and 50 wt% LP with respect to PU) nanoparticles (NPs) were analyzed using FE-SEM, FTIR, and XRD experimental analyzers. Electron microscopy and spectroscopy indicated that the proper content of LP NPs is homogeneous dispersion in a polymer matrix. In addition, 50 wt% of LP results in a higher concentration spinning nanosuspension that leads to some agglomeration on the film surface. The chloroform, benzene, and toluene (VOCs) absorption capacity of PU/LP composite films showed a trend of toluene > benzene > chloroform. The highest VOC absorption capacity was found with PU composite mats containing 30 wt% LP NPs. The high VOC absorption capacity of PU/LP composite films can be used to remove VOCs from a new house or car.